Systematic review of strategies to reduce the gender gap in engineering training: progress, challenges and opportunities towards equity - Olivos Jiménez, Milagros Antonieta; Ramos Farroñán, Emma Verónica; Otiniano León, Mabel Ysabel; Lizarzaburu Aguinaga, Danny Alonso; Paredes Morales, Ana Elizabeth; Pereyra Gonzales, Tony Venancio; Arbulú Castillo, Julie Catherine (LACCEI, 2025)
This study addresses the persistent gender gap in engineering fields, analyzing the most effective interventions to reduce it in higher education. It highlights the social, institutional, and psychological barriers that perpetuate the underrepresentation of women in engineering and explores interventions such as mentoring programs, curriculum transformation, and the application of Social Cognitive Theory and Self-Determination Theory to promote gender equality. The review identifies the influence of contextual factors, such as socio-economic and cultural differences, on the effectiveness of these strategies. Additionally, it emphasizes the need for longitudinal research and integrated approaches to address educational, sociocultural, and institutional barriers. The study underscores the importance of linking local initiatives with the Sustainable Development Goals to promote gender equity in engineering education.